Trends and distribution of malaria among children under five in Tamale Metropolis in Ghana, amidst interventions: Analysis of surveillance and program data, 2017 -2021 - Shahadu Shembla Sayibu; Basil Benduri Kaburi; Dora Dadzie; Delia Bandoh; Isaac Baffoe-Nyarko; Charles Lwanga Noora; Abdul Gafaru Mohammed; Francis Genye Salifu; Peter Apetorgbor; Paul Hilarius Asiwome Kosi Abiwu; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: Despite the distribution of insecticide-treated nets (ITN), and seasonal malaria chemoprevention (SMC) in Tamale Metropolis, the malaria burden started increasing in 2021. We described the distribution and trends of malaria cases; and evaluated SMC and ITN coverages among children under five years (under-5). Methods: Data sources were District Health Information Management System II (DHIMS II) at Tamale Metropolis from 2017 – 2021, Ghana Malaria Control Program reports, Ghana Expanded Program on Immunization and the Ghana Statistical Services. Variables included: under-5 malaria cases (tested or not tested) and deaths; ITN distributed to under-5s; and SMC doses distributed. We computed percentages, constructed CUSUM-2 thresholds for trend analysis. SMC and ITN coverages were extracted from the DHIMS II as pre-populated indicators (i.e., children under-5 who got an ITN at measles-2 vaccination, and those who received SMC per cycle). We compared findings with WHO targets. Results: Total malaria cases among children under five years were 50,379. Children 1-4years old accounted for 74.8% (37697/50379). Presumptively-treated cases were 79.28% (13694/17272) in 2017, 54.4% (9586/17626) in 2018, 48.5% (6294/12976) in 2019, 2.1% (144/6742) in 2020 and 10.33% (875/8471) in 2021. Total malaria cases decreased from 2,300 in January 2017 to 300 mid-period, rising to 1000 from July 2020; seasonal (July-November) peaks followed similar trends. Mean ITN coverage was 50.8%, while SMC cycle coverages were all below 90%. Conclusion: While malaria cases resurged in 2021, case fatality rates increased throughout the period. Presumptive treatment rates decreased, though, still above WHO target. This inflated neonatal malaria cases. SMC and ITN coverages were poor, suggesting why malaria cases increased. Findings informed facilitation of health workers’ discussion forum on adherence to the WHO’s Test, Treat and Track strategy and boosting of ITN and SMC coverage, as well as audit into cases and deaths.